A Multicentre UK Study of Outcomes of Nasopharyngeal Carcinoma Treated With Intensity-Modulated Radiotherapy ± Chemotherapy. Issue 4 (April 2020) - Slevin, F.; Pan, S.; Mistry, H.; Sen, M.; Foran, B.; Slevin, N.; Dixon, L.; Thomson, D.; Prestwich, R.
Abstract: Aims: To report the outcomes of nasopharyngeal carcinoma in adults across three large centres in a non-endemic region in the era of intensity-modulated radiotherapy (IMRT). Materials and methods: Adult patients with nasopharyngeal carcinoma treated in three large cancer centres with IMRT ± chemotherapy with curative intent between 2009 and 2016 were identified from institutional databases. Radiotherapy was delivered with 70 Gy in 33–35 daily fractions. A univariable analysis was carried out to evaluate the relationship of patient, tumour and treatment factors with progression-free survival (PFS) and overall survival. Results: In total, 151 patients were identified with a median follow-up of 5.2 years. The median age was 52 years (range 18–85). Seventy-five per cent were of Caucasian origin; 75% had non-keratinising tumours; Epstein Barr virus status was only available in 23% of patients; 74% of patients had stage III or IV disease; 54% of patients received induction chemotherapy; 86% of patients received concurrent chemotherapy. Five-year overall survival, PFS, local disease-free survival, regional disease-free survival and distant disease-free survival were 70%, 65%, 91%, 94% and 82%, respectively. Keratinising squamous cell carcinoma, older age, worse performance status, smoking and alcohol intake were associated with inferior overall survival and PFS. Conclusions: Local, regional and distant disease control are relatively high following IMRT ± chemotherapy in a non-endemic population. There was considerable heterogeneity in terms of radiotherapy treatment and the use of chemotherapy, encouraging the development of treatment protocols and expert peer review in non-endemic regions. Highlights: Multicentre UK outcomes of treatment of nasopharyngeal carcinoma. Comparable local, regional and distant disease control with other non-endemic series. Variation identified in radiotherapy and chemotherapy treatment strategies.